2018
DOI: 10.1111/bph.14088
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of knockout mice to clarify the role of the opioid system in chronic pain

Abstract: This article is part of a themed section on Emerging Areas of Opioid Pharmacology. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.14/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 158 publications
0
29
0
Order By: Relevance
“…Our results with Nav1.8‐MOP knockouts show lack of pronociceptive effects of MOP expressed in sensory neurons, in contrast to the previously described involvement of peripheral MOP in opioid‐induced pronociception (Corder et al, ). Differences in the targeted neuronal populations (Nav1.8+ vs. TRPV1+ neurons) or in the genetic background of the knockout lines (Maldonado et al, ) may have contributed to these divergent results. Potentiation of C‐fibre synapses by enhancing NMDA receptors activity (Heinl, Drdla‐Schutting, Xanthos, & Sandkühler, ), descending facilitation (Dogrul, Ossipov, & Porreca, ), coupling of MOP to excitatory G proteins (Tsai et al, ; Wang, Friedman, Olmstead, & Burns, ), recruitment of spinal ionotropic glutamate receptors (Cabañero et al, ) or decrease in DOP mRNA expression (Cabañero et al, ) are some of the mechanisms triggered by MOP activation that may contribute to the excitatory effects of MOP in mice with chronic neuropathic pain (Martínez‐Navarro, Maldonado, & Baños, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results with Nav1.8‐MOP knockouts show lack of pronociceptive effects of MOP expressed in sensory neurons, in contrast to the previously described involvement of peripheral MOP in opioid‐induced pronociception (Corder et al, ). Differences in the targeted neuronal populations (Nav1.8+ vs. TRPV1+ neurons) or in the genetic background of the knockout lines (Maldonado et al, ) may have contributed to these divergent results. Potentiation of C‐fibre synapses by enhancing NMDA receptors activity (Heinl, Drdla‐Schutting, Xanthos, & Sandkühler, ), descending facilitation (Dogrul, Ossipov, & Porreca, ), coupling of MOP to excitatory G proteins (Tsai et al, ; Wang, Friedman, Olmstead, & Burns, ), recruitment of spinal ionotropic glutamate receptors (Cabañero et al, ) or decrease in DOP mRNA expression (Cabañero et al, ) are some of the mechanisms triggered by MOP activation that may contribute to the excitatory effects of MOP in mice with chronic neuropathic pain (Martínez‐Navarro, Maldonado, & Baños, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, opioid analgesics remain the cornerstone for the management of moderate to severe nociceptive and inflammatory pain (Carroll, Angst, & Clark, 2004). However, the function of these opioid receptors during neuropathic pain is not well understood, with several conflicting results showing increased, unchanged or reduced pain sensitization in different MOP knockouts and animal models of neuropathic pain (Maldonado, Baños, & Cabañero, 2018). Likewise, controversy also exists about the long-term efficacy and safety of MOP opioids controlling neuropathic pain in human beings (Finnerup et al, 2015;Kalso, Edwards, Moore, & McQuay, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The quest for novel opioidergic drugs is a dynamic and topical theme, especially because the well-described adverse effects of conventional opioid analgesics have recently escalated into a major crisis, resulting in thousands of deaths, particularly in the US. Therefore, while the focus has been traditionally on MOR agonists, recent efforts have addressed the therapeutic potential of other receptors as well as their localization in distinct avenues of nociceptive pathways (Maldonado et al, 2018). Indeed, the abundance of opioid receptor expression throughout the pain pathway makes harnessing them pharmacologically a double-edged sword.…”
mentioning
confidence: 99%
“…Mice carrying sensory-neuron-specific conditional knockout alleles emerged as a gold standard to investigate these differential contributions. For the first time, it was possible to show that a loss of peripheral cannabinoid receptor 1 leads to a marked attenuation of the analgesic effects of systemically applied cannabinoids (Agarwal et al, 2007), and a similar strategy was used to demonstrate that DOR agonists have strongly diminished analgesic effect in mice lacking DORs in primary afferents (Gaveriaux-Ruff et al, 2011;Maldonado et al, 2018). MOR-mediated analgesia was also found to be impaired in inflammatory pain in mice lacking MORs specifically in peripheral sensory neurons (Maldonado et al, 2018).…”
mentioning
confidence: 99%
“…One further contribution to the discussion of opioids in chronic pain is provided by Maldonado et al . (), who describe the effects of various gene knockouts in mice of components of the opioid system (receptors or peptides) on models of chronic pain. The data from such studies have suggested, for example, the development of novel opioid drugs which target multiple opioid receptor subtypes.…”
mentioning
confidence: 99%